Five egg-laying queens in a single colony of brazilian stingless bees (Melipona scutellaris Latreille - Lopes de Carvalho, Carlos Alfredo; Souza, Bruno Almeida de; Dias, Carleandro de Souza; Alves, Rogério Marcos Oliveira de; Melo, Alex Fábio de Lima; Soares, Ana Cristina Fermino; Carvalho-zilse, Gislene Almeida (Acta Amazonica, 2011)
Polygyny, characterized by the presence of several egg-laying queens, is considered as a temporary colony status. In stingless bees it is rarely observed. This paper reports the first case of natural polygyny in Melipona scutellaris colony, with five egg-laying queens.
Presença de cinco rainhas fisogástricas em colônia de abelha sem ferrão (Melipona scutellaris Latreille)
Keywords: Meliponini; "uruçu" Stingless Bee; Physogastric Queens; Meliponini; Abelha Uruçu; Rainhas Fisogástricas